2018
DOI: 10.1039/c8cc03727b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a NIR absorbing thienyl curcumin contrast agent for photoacoustic imaging

Abstract: The synthesis and characterization of a bis(2-dimethylaminothien-5-yl)curcumin boron difluoride chromophore is presented. Photophysical, electrochemical and computational investigations establish the properties of its absorption in the Vis-NIR spectral range relative to established curcumin dyes. Application of this thienyl curcumin dye as a photoacoustic contrast agent is investigated against the dicarbocyanine Cy5 dye in the 675-735 nm excitation range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…[ 16 ] To date, FDA‐approved indocyanine green (ICG) is widely studied as (off‐label) PA probe, despite its low PA‐signal and short blood half‐life. [ 17 ] Other small organic chromophores, e.g., azo‐dyes, [ 18 ] (na)phthalocyanines, [ 15b,19 ] IR‐dye fluorophores, [ 15a,20 ] (aza)BODIPYs, [ 21 ] porphyrins, [ 22 ] and other dyes [ 23 ] were also explored for PAI applications. Several of the above named probes could also be used in photothermal therapy (PTT), [ 24 ] as both applications share a similar underlying principle, optical absorption to thermal conversion via nonradiative process.…”
Section: Figurementioning
confidence: 99%
“…[ 16 ] To date, FDA‐approved indocyanine green (ICG) is widely studied as (off‐label) PA probe, despite its low PA‐signal and short blood half‐life. [ 17 ] Other small organic chromophores, e.g., azo‐dyes, [ 18 ] (na)phthalocyanines, [ 15b,19 ] IR‐dye fluorophores, [ 15a,20 ] (aza)BODIPYs, [ 21 ] porphyrins, [ 22 ] and other dyes [ 23 ] were also explored for PAI applications. Several of the above named probes could also be used in photothermal therapy (PTT), [ 24 ] as both applications share a similar underlying principle, optical absorption to thermal conversion via nonradiative process.…”
Section: Figurementioning
confidence: 99%
“…ACS reagent grade toluene, tetrahydrofuran, dichloromethane and hexane for synthesis were purchased from Pharmco Aaper. 1 , 2 , DMA‐2 , DMA‐3 , 4 and DMA‐4 have been previously reported . 3 , 5 and DMA‐5 were prepared using a previously reported standard procedure from the commercially available 5‐dimethylamino‐thiophene‐2‐carbaldehyde, and the prepared 5‐ald and DMA‐5‐ald , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…As is discussed in detail below, DMA functionalization serves to destabilize the HOMO level of the curcuminoid dye thus decreasing their HOMO–LUMO band gap. This is responsible for shifting their absorbance toward the near NIR . In a prior study, we demonstrated that the naphth‐4‐yl substituted curcumin 4 exhibits the most impressive reverse saturable absorption and nonlinear PA emission of any curcumin dye studied to date .…”
Section: Introductionmentioning
confidence: 92%
“…[19] Other groups also reported interesting photophysical ande lectronic properties of curcuminoids-BF 2 , [20] including charge transport in nanojunctions [21] and enhanced photoacousticr esponses. [22] Single-crystal X-ray diffraction studies have shown that curcuminoid backbones interact strongly in p-stacks. [5] The monochromophoric compound R-Me ( Figure 1) provides at ypical example of such tightly packed dye molecules in the crystal.…”
Section: Quadrupolar-like D-p-a-p-d (Or A-p-d-p-a) Chromophoresmentioning
confidence: 99%
“…Depending on the nature of the terminal electron‐donor groups, they display a broad range of optical and electronic properties in the solid state, such as near‐infrared fluorescence emission, thermally assisted delayed fluorescence, two‐photon excited fluorescence, amplified spontaneous emission, and charge separation in bulk heterojunction organic solar cells . Other groups also reported interesting photophysical and electronic properties of curcuminoids‐BF 2 , including charge transport in nanojunctions and enhanced photoacoustic responses . Single‐crystal X‐ray diffraction studies have shown that curcuminoid backbones interact strongly in π‐stacks .…”
Section: Introductionmentioning
confidence: 99%